Investigating the role of information technology system integration, user acceptance and information technology satisfaction and security on efficiency and accuracy of immigration documents processing - Wilonotomo Wilonotomo; Mochamad Ryanindityo; Koesmoyo Ponco Aji; Anindito Rizki Wiraputra; Sri Kuncoro Bawono; Intan Nurkumalawati; Trisapto Wahyudi Agung Nugroho; Budy Mulyawan (International Journal of Data and Network Science, 2025)
Technological transformation not only changes the way we communicate and do business but also changes the way the government provides public services to the community. One manifestation of this transformation is the implementation of Information Systems (IS) for public services, to provide services that are more efficient, transparent, and responsive. By implementing an IS, the administration and data management process becomes more efficient. This research method uses a quantitative method approach, The research data are obtained by distributing online questionnaires via the Google Form platform and the respondents for this research were 576 senior employees of the immigration department in Indonesia who were determined using a simple random sampling method. Research data analysis uses structural equation modeling (SEM). The variables in this research are the dependent variables, namely information Technology System integration and Information Technology System Security (ITSS). The dependent variable is the Efficiency and Accuracy of Immigration Documents (EAID) and User Acceptance and Satisfaction (UAS). Based on data analysis, it is concluded that TSS integration had a positive and significant relationship with EAID, Information technology system integration had a positive and significant relationship with UAS, ITSS had a positive and significant relationship with EAID, ITSS had a positive and significant relationship with UAS and user acceptance and satisfaction had a positive and substantial relationship with the EAID. Implementing IS opens the door to more efficient, transparent, and responsive public services. By leveraging technology, governments can streamline administrative processes, increase citizen participation, and create an environment where every citizen can benefit from better public services. In carrying out this transformation, the government must remain focused on data security, privacy, and community empowerment so that people truly feel the positive impact of technological developments in public services.